Anatomical and clinical aspects of aberrant right subclavian artery - Lepich, Tomasz; Karaś, Radosław; Kania, Kamil; Bajor, Grzegorz (Medical Studies/Studia Medyczne, 2023)
Atrophy of the fourth right aortic arch during embryogenesis can lead to arteria lusoria. This occurs with a frequency of 0.5–2%. This artery originates directly from the aortic arch as a fourth branch or from the proximal part of the descending aorta. Then it follows an upward and rightward direction crossing the trachea and esophagus in its course. This abnormal artery is accompanied in 20–60% of cases by dilatation of its proximal part, called Kommerell’s diverticulum. A correlation has been noted between the presence of arteria lusoria and chromosomal aberrations, mainly Down syndrome. Arteria lusoria in fetuses is diagnosed using ultrasound, and in adults, the gold diagnostic standard is computed tomography or magnetic resonance angiography. Consequences of arteria lusoria may include dysphagia (dysphagia lusoria), chronic cough, arterio-oesophageal fistula, retrosternal pain, respiratory problems, and numbness of the right upper limb. Respiratory disorders accompanying arteria lusoria occur mainly in children because their trachea is less rigid than in adults and more prone to deformation. Arteria lusoria is a clinically significant marker of fetal congenital malformations. It also may be a cause of non-specific symptoms in children and adults that should be considered during differential diagnosis.